Portable random number generators - Jr. Gerald P. Dwyer; K. B. Williams (Federal Reserve Bank of Atlanta, 1999)
Computers are deterministic devices, and a computer-generated random number is a contradiction in terms. As a result, computer-generated pseudorandom numbers are fraught with peril for the unwary. We summarize much that is known about the most well-known pseudorandom number generators: congruential generators. We also provide machine-independent programs to implement the generators in any language that has 32-bit signed integers-for example C, C++, and FORTRAN. Based on an extensive search, we provide parameter values better than those previously available.
Keywords: 330; Programming (Mathematics); Computers